Influence of ball-in-play time on the activity profiles of rugby league match-play - Gabbett, T. J. (The Journal of Strength and Conditioning Research, 2015)
Most investigations of the activity profiles of rugby league match-play have reported the physical demands across the entire match irrespective of stoppages in play. This study investigated the activity profiles of rugby league match-play, accounting for time when the ball was "in" and "out-of-play." One-hundred four players (mean age, 24.0 ± 3.0 years) from 11 semiprofessional rugby league teams underwent global positioning system analysis during 22 matches. Matches were coded for activity and recovery cycles. Time when the ball was continuously in play was considered activity, whereas any stoppages during the match (e.g., for scrums, penalties, line drop-outs, and tries) were considered recovery. The relative distance (125.1 ± 16.1 m/min vs. 86.7 ± 9.8 m/min), low-speed activity (115.3 ± 15.7 m/min vs. 81.7 ± 9.8 m/min), and high-speed running (9.5 ± 2.9 m/min vs. 5.0 ± 1.8 m/min) demands were significantly (p < 0.0001) higher when accounting for ball-in-play time. The frequency of collisions (0.67 ± 0.28 per minute vs. 0.41 ± 0.17 per minute) and repeated high-intensity effort (RHIE) bouts (1 every 6.1 ± 4.7 minutes vs. 1 every 10.7 ± 8.3 minutes) were also higher when stoppage time was excluded. Large negative correlations (p = 0.001) were found between total ball-in-play time and relative measures of total distance (r = -0.67) and low-speed activity (r = -0.60). These results demonstrate the greater movement, contact, and RHIE demands when rugby league time-motion data are expressed relative to ball-in-play time. Furthermore, the reduction in relative intensity with longer total ball-in-play time suggests that during prolonged passages of play, players adopt a pacing strategy to maintain high-intensity performance and manage fatigue.